Open Colectomies of Shorter Operative Time Do Not Result in Improved Outcomes Compared With Prolonged Laparoscopic Operations. Issue 5 (October 2017) - Zettervall, Sara L.; Haskins, Ivy N.; Deery, Sarah E.; Amdur, Richard L.; Lin, Paul P.; Vaziri, Khashayar
Abstract : Background: Laparoscopic colectomies are associated with reduced perioperative morbidity and mortality compared with open surgery. Nevertheless, many surgeons continue to utilize an open surgical approach due to the perceived benefits of shorter operative times. This study aims to compare the outcomes of laparoscopic versus open colectomies of equal or shorter operative duration. Methods: All patients undergoing elective laparoscopic or open colectomy in the American College of Surgeons National Surgical Quality Improvement Project (ACS-NSQIP) were identified from the years 2005 through 2012. Patients were stratified first by operative procedure including partial colectomy, total colectomy, or low anterior resection. Each surgical group was then divided into 4 groups according to operative time: <90 minutes, ≥90 minutes and <3 hours, ≥3 hours and <6 hours, and ≥6 hours. In total, 30-day outcomes were compared between laparoscopic operations and open procedures of shorter or equivalent durations within each surgical group. Multivariate logistic regression was utilized to account for differences in patient demographics and comorbidities between the surgical groups. Results: In total, 156, 503 patients met inclusion criteria; 112, 053 (71.6%) patients underwent a partial colectomy, 13, 838 (8.8%) patients underwent a total colectomy, and 30, 612 (19.6%) patients underwent a low anterior resection. A laparoscopic approach was used in 34% (37, 789 patients) of the partial colectomies performed, 31% (4285 patients) of the total colectomies performed, and 45% (13, 850 patients) of the low anterior resections performed. For all procedures, laparoscopic operations <6 hours were associated with superior outcomes compared with shorter open procedures. The benefit of laparoscopic operations was lost when operative time exceeded 6 hours. Conclusions: Laparoscopic colectomies are associated with improved outcomes compared with open operations that do not exceed an operative time of 6 hours. Given the potential to improve patient outcomes, consideration should be given to the laparoscopic approach for all colon surgeries expected to be completed in <6 hours.